Materiality: An Empirical Study of Actual Auditor Decisions (Book). - Boatsman, James R.; Brief, Richard P. (The Accounting Review, 1987)
Reviews the book "Materiality: An Empirical Study of Actual Auditor Decisions," by Chris Robinson and Len Fertuck.